Entre la conservación del bosque y el crecimiento de la ciudad: las localidades rurales en el espacio periurbano del Huitepec en San Cristóbal de Las Casas, Chiapas, México - Calderón Cisneros, Araceli; Soto Pinto, Lorena; Estrada Lugo, Erin (El Colegio de México A.C., 2012)
Urban growth affects the agricultural and forest areas located in its immediate vicinity, transforming traditional forms of land control and use. Very little information is available on the patterns of this process in medium-sized cities, particularly if the information is provided from the perspective of local actors. This article presents a case study that analyzes the influence of the growth of the city of San Cristóbal de Las Casas, Chiapas, on an adjacent rural area and its effects on forest and farm areas. Although there is an intense process of urbanization, marked by a population increase, the fragmentation of land ownership and the arrival of urban services, some forest areas have been maintained in nature reserves and spaces associated with agricultural and urban uses, forming an agro-forest landscape that provides natural resources and environmental services for the local and urban population, foremost among which is recharging the aquifers. This appears to correspond to a new rurality in which urban and rural socio-environmental processes are spatially integrated and where the forest and agriculture have a different meaning and value for the actors there, which often contradict each other.